From Chemistry to Pharmacology: Exploring the Anti-Inflammatory and Antioxidant Potential of Novel Dexketoprofen Amide Derivatives - Marko Karović; Miloš Nikolić; Nikola Nedeljković; Marina Vesović; Marina Nikolić; Marijana Anđić; Nevena Lazarević; Vladimir Jakovljević; Jelena Nedeljković; Sanja Đaković; Jelena Bošković; Vladimir Dobričić (Antioxidants)
In the present study, five novel dexketoprofen amide derivatives with a free carboxyl group in their side chains were synthesized. The in vivo anti-inflammatory potential of dexketoprofen derivatives was evaluated using a carrageenan-induced paw edema model of acute inflammation. Additionally, the local and systemic redox status in rats following acute administration of the compounds was assessed by measuring levels of pro-oxidative markers and the activity of antioxidant enzymes. Among the analyzed molecules, derivatives 2 and 4 exhibited the most potent in vivo anti-inflammatory activity, showing effects comparable to those of the parent compound dexketoprofen. In vitro results revealed that all newly synthesized compounds exhibited low inhibitory activity toward COX-1, whereas only compound 4 showed significant COX-2 inhibition. The stronger binding affinity of derivative 4 for COX-2 in comparison to other tested compounds is likely attributed to its ability to form multiple electrostatic interactions within the enzyme’s active site. Furthermore, compounds 2 and 5 demonstrated efficacy comparable to the parent drug in restoring redox balance, indicating their potential antioxidant properties under acute inflammatory conditions. The findings of this study underscore the therapeutic potential of the novel dexketoprofen amide derivatives as dual-function agents with the capacity to modulate both inflammatory responses and oxidative stress.